1986
DOI: 10.1099/00207713-36-1-86
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Herbaspirillum seropedicae gen. nov., sp. nov., a Root-Associated Nitrogen-Fixing Bacterium

Abstract: During a survey of the occurrence of Azospirillum spp. in cereal roots, we obtained 119 isolates which could not be identified as members of one of the three previously described Azospirillum species. These strains formed a very homogeneous group of N2-fixing, microaerobic, motile, vibrioid, gram-negative rod-shaped organisms which formed a veillike pellicle in semisolid medium similar to that of Azospirillum spp. However, the new isolates differed from Azospirillum spp. by their smaller cell width (0.6 to 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
244
0
33

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(287 citation statements)
references
References 23 publications
3
244
0
33
Order By: Relevance
“…Herbaspirillum strains were previously shown to be involved in nitrate reduction of rice paddy soil (Ishii et al, 2009b, but the present study showed that they are also important players in N 2 O reduction. Although some Herbaspirillum species (for example, Herbaspirillum seropedica) can colonize rice roots and stems and fix atmospheric N 2 (Baldani et al, 1986;Elbertagy et al, 2001), almost all strains obtained in this study did not show N 2 -fixing ability (S. Ishii, unpublished data). In addition, 16S rRNA gene similarities between the Herbaspiriilum strains obtained in this study and other Herbaspirillum species were o97%.…”
Section: Discussionmentioning
confidence: 99%
“…Herbaspirillum strains were previously shown to be involved in nitrate reduction of rice paddy soil (Ishii et al, 2009b, but the present study showed that they are also important players in N 2 O reduction. Although some Herbaspirillum species (for example, Herbaspirillum seropedica) can colonize rice roots and stems and fix atmospheric N 2 (Baldani et al, 1986;Elbertagy et al, 2001), almost all strains obtained in this study did not show N 2 -fixing ability (S. Ishii, unpublished data). In addition, 16S rRNA gene similarities between the Herbaspiriilum strains obtained in this study and other Herbaspirillum species were o97%.…”
Section: Discussionmentioning
confidence: 99%
“…G. diazotrophicus está inserida no grupo das bactérias do ácido acético e foi isolada de raízes e parte aérea de cana-de-açúcar por Cavalcante & Döbereiner (1988). Já as bactérias do gênero Herbaspirillum são naturalmente associadas às gramíneas e aí se incluem as espécies H. seropedicae e H. rubrisubalbicans (Baldani et al, 1986(Baldani et al, , 1996.…”
Section: Introductionunclassified
“…Tal diversidade garante não só a resiliência da FBN nos ecossistemas, como também a ocorrência deste processo nos mais diferentes habitats terrestres (Moreira & Siqueira, 2002). Em geral, espécies de bactérias diazotróficas associativas têm sido isoladas de raízes e partes aéreas de gramíneas de pastagem e de grãos (Magalhães & Döbereiner, 1984;Baldani et al, 1986;Döbereiner, 1992;Baldani, 1996;Dicello et al, 1997, Eckert et al, 2001, de tubérculos (Balota et al, 1997), cafeeiros (Santos et al, 2001) e fruteiras (Magalhães & Döbereiner, 1984;Weber et al, 2001).…”
Section: Introductionunclassified